(untitled) (International Journal of Nursing Education, 2019)
The Clinical placements and clinical learning form a major part of nurse education and have an important role in students’ perceptions of nursing. This study assessed the perceptions of male nursing students, their views, concerns, challenges in providing care to the children during paediatric clinical placement. A Descriptive, qualitative design with focus group interview was conducted. Analysis of data yielded four themes: 1) Traditionally gendered specialty; 2) Barriers to provision of care; 3) Lack of support; 4) Alternative clinical settings.